If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + bx = -4 Solving ax + bx = -4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1bx' to each side of the equation. ax + bx + -1bx = -4 + -1bx Combine like terms: bx + -1bx = 0 ax + 0 = -4 + -1bx ax = -4 + -1bx Divide each side by 'x'. a = -4x-1 + -1b Simplifying a = -4x-1 + -1b Reorder the terms: a = -1b + -4x-1
| X=10x-78 | | 3x+4x=6x-8 | | 2x+5+2x-23=90 | | -5+b/8=-4 | | -7(x+3)=3(-5-2x) | | 19=-3+4(v-6) | | 2(x+3)-3x-7=2 | | x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= | | -2-9r=10+2r+10 | | 20(16x+8)=12 | | 7-10n+5n=18-96 | | x^4-4x^3+4x^2-36x-45=0 | | 3f=8-5f | | 2.1x-8.9=3.9x-8.9-1.8x | | X-4y=3b | | 3(x-1)=2x-3+3 | | 8w=9+9w | | 6x^2-10x-7=0 | | (x/4)+8=-8 |